Low-temperature sintering of temperature-stable LaNbO4 microwave dielectric ceramics - Lee, Hang-Won; Park, Jeong-Hyun; Nahm, Sahn; Kim, Dong-Wan; Park, Jae-Gwan (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
We demonstrate the correlation between sintering behavior and microstructural observations in low-temperature sintered, LaNbO4 microwave ceramics. Small CuO additions to LaNbO4 significantly lowered the sintering temperature from 1250 to 950 degrees C. To elucidate the sintering mechanism, the internal microstructure of the sample manipulated by a focused ion beam (FIB) was investigated using transmission electron microscopy (TEM) and energy-dispersive spectroscopy (EDS). LaNbO4 with 3 wt% CuO sintered at 950 degrees C for 2 h possessed the following excellent microwave dielectric properties: a quality factor (Qxf) of 49,000 GHz, relative dielectric constant (epsilon(r)) of 19.5, and temperature coefficient of resonant frequency (tau(f)) of 1 ppm/degrees C. The ferroelastic phase transformation was also investigated using in situ X-ray diffraction (XRD) to explain the variation of tau(f) in low-temperature sintered LaNbO4 as a function of CuO content. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: RARE-EARTH ORTHONIOBATE; BEHAVIOR